2009
DOI: 10.1080/13501760902872643
|View full text |Cite
|
Sign up to set email alerts
|

Economic interests and public support for the euro

Abstract: Although economic theories have been advanced to explain public support for the common currency, we know very little about how public support for the euro has been affected by its economic impact. We hypothesize that concern about rising prices following the introduction of the euro may have dampened enthusiasm for the project. We use Eurobarometer data from 2000 -2007 to examine how rising prices and other economic factors have shaped support for the euro. We find that while inflation has had a negative impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 24 publications
9
56
0
Order By: Relevance
“…Support for monetary integration has also been explained in utilitarian terms, arguing that individuals with high involvement in international trade should favour the euro more than individuals employed in the non-tradable sector (Banducci et al 2009;Gabel 2001;Gabel and Hix 2005). Studies of support for the euro have also found that sociotropic economic concerns play a role: citizens in countries that benefit economically, or are perceived to benefit economically, from membership of the EU are more supportive of the euro (Banducci et al 2003(Banducci et al , 2009Hobolt and Leblond 2014;Kaltenthaler and Anderson 2001). An alternative explanation for the variation in support for European integration, and the euro more specifically, focuses less on economic self-interest and more on the threat that European integration can pose to national identity and a country's symbols and values (Carey 2002;Hooghe and Marks 2004;McLaren 2006).…”
Section: Public Opinion and European Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for monetary integration has also been explained in utilitarian terms, arguing that individuals with high involvement in international trade should favour the euro more than individuals employed in the non-tradable sector (Banducci et al 2009;Gabel 2001;Gabel and Hix 2005). Studies of support for the euro have also found that sociotropic economic concerns play a role: citizens in countries that benefit economically, or are perceived to benefit economically, from membership of the EU are more supportive of the euro (Banducci et al 2003(Banducci et al , 2009Hobolt and Leblond 2014;Kaltenthaler and Anderson 2001). An alternative explanation for the variation in support for European integration, and the euro more specifically, focuses less on economic self-interest and more on the threat that European integration can pose to national identity and a country's symbols and values (Carey 2002;Hooghe and Marks 2004;McLaren 2006).…”
Section: Public Opinion and European Integrationmentioning
confidence: 99%
“…From a utilitarian perspective, generic support for European integration is determined by a rational cost -benefit analysis: those who benefit economically from European integration (particularly trade liberalization) are supportive, whereas those who stand to lose are more hostile (Gabel 1998;Gabel and Palmer 1995;McLaren 2006). Support for monetary integration has also been explained in utilitarian terms, arguing that individuals with high involvement in international trade should favour the euro more than individuals employed in the non-tradable sector (Banducci et al 2009;Gabel 2001;Gabel and Hix 2005). Studies of support for the euro have also found that sociotropic economic concerns play a role: citizens in countries that benefit economically, or are perceived to benefit economically, from membership of the EU are more supportive of the euro (Banducci et al 2003(Banducci et al , 2009Hobolt and Leblond 2014;Kaltenthaler and Anderson 2001).…”
Section: Public Opinion and European Integrationmentioning
confidence: 99%
“…Although citizens' perceptions might influence citizens' systemic trust (Banducci et al, 2009, p. 572) this paper solely focuses on the impact of the "classical" three macro economic variables: 4 i) inflation, ii) growth of GDP per capita and iii) unemployment when trying to identify those factors that led to a loss of citizens' trust in the ECB. This undertaking seems to be reasonable for three reasons.…”
Section: Possible Factors Informing Citizens' Trust In the Ecbmentioning
confidence: 99%
“…Therefore, when estimating the credibility of a monetary regime one should prefer subjective attitudes to observing changes in variables that are considered to be "good proxies". Finally, the analysis of subjective attitudes captured in survey responses draws support from Roth et al (2012, p.14) who cite Banducci et al (2009) to the effect that 'actual economic reality -as summarised in official economic statisticsdoes not necessarily agree with the perceived economic situation'.…”
Section: Credibility Of a Cbamentioning
confidence: 96%